Turbulent flow evaluation of the venous needle during hemodialysis - Unnikrishnan, Sunil; Huynh, Thanh N.; Anayiotos, Andreas (My University, 2005)
Arteriovenous (AV) grafts and fistulas used for hemodialysis frequently develop intimal hyperplasia (IH) at the venous anastomosis of the graft, leading to flow-limiting stenosis, and ultimately to graft failure due to thrombosis. Although the high AV access blood flow has been implicated in the pathogenesis of graft stenosis, the potential role of needle turbulence during hemodialysis is relatively unexplored. High turbulent stresses from the needle jet that reach the venous anastomosis may contribute to endothelial denudation and vessel wall injury. This may trigger the molecular and cellular cascade involving platelet activation and IH, leading to eventual graft failure. In an in-vitro graft/needle model dye injection flow visualization was used for qualitative study of flow patterns, whereas laser Doppler velocimetry was used to compare the levels of turbulence at the venous anastomosis in the presence and absence of a venous needle jet. Considerably higher turbulence was observed downstream of the venous needle, in comparison to graft flow alone without the needle. While turbulent RMS remained around 0.1 m/s for the graft flow alone, turbulent RMS fluctuations downstream of the needle soared to 0.4-0.7 m/s at 2 cm from the tip of the needle and maintained values higher than 0.1 m/s up to 7-8 cm downstream. Turbulent intensities were 5-6 times greater in the presence of the needle, in comparison with graft flow alone. Since hemodialysis patients are exposed to needle turbulence for four hours three times a week, the role of post-venous needle turbulence may be important in the pathogenesis of AV graft complications. A better understanding of the role of needle turbulence in the mechanisms of AV graft failure may lead to improved design of AV grafts and venous needles associated with reduced turbulence, and to pharmacological interventions that attenuate IH and graft failure resulting from turbulence.
Keywords: Hemodialysis; Hyperplasia; Arteriovenous anastomosis